1982
DOI: 10.1002/jcp.1041130220
|View full text |Cite
|
Sign up to set email alerts
|

Complementary recessive 25‐hydroxycholesterol‐resistant somatic cell mutants – assay of 25‐hydroxycholesterol binding activity

Abstract: Complementation analysis of recessive 25-hydroxycholesterol-resistant mutants of the CHO-Kl cell shows the existence of at least two complementation groups, one of which is missing a binding activity for 25-hydroxycholesterol. Both complementation groups are shown to be refractory to inhibition of cellular HMG-CoA reductase activity and in the inhibition of biosynthesis of this enzyme by 25-hydroxycholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We called these cells sterol regulatory-defective (SRD-1, -2, and -3) cells (25,26). Similar sterolresistant cell lines were reported from the laboratories of Kandutsch (27), Sinensky (28,29), and Chang (30,31).…”
Section: Mutant Mammalian Cells With Defects In Cholesterol Homeostassupporting
confidence: 81%
“…We called these cells sterol regulatory-defective (SRD-1, -2, and -3) cells (25,26). Similar sterolresistant cell lines were reported from the laboratories of Kandutsch (27), Sinensky (28,29), and Chang (30,31).…”
Section: Mutant Mammalian Cells With Defects In Cholesterol Homeostassupporting
confidence: 81%
“…This is further extended by the results discussed below, but is also in agreement with effects observed in rat liver, where mevinolin (an analogue of compactin; Alberts et al, 1980) increased (Clarke et al, 1983) and mevalonate decreased (Clarke et al, 1984) the reductase mRNA content, whereas mevalonate enhanced the enzyme degradation . Further, it was noted that mevinolin prevented HMG-CoA reductase enzyme degradation in Chinese-hamster ovary cells (Sinensky & Logel, 1983). Comparable effects of compactin and mevalonate on reductase mRNA contents were measured in UT-I cells (Luskey et al, 1983), a Chinese-hamster ovary mutant cell line, resistant to compactin , by a stable amplification of the reductase gene (Luskey et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Early somatic cell genetic characterization indicated that there was genetic diversity in such mutants and that some were recessive (13,14). The class 1 and 2 mutants, whose defects are now known, are dominant (or co-dominant) mutations.…”
mentioning
confidence: 99%